Genotype x environment interaction and stability of indigenous coriander (Coriandrum sativum L.) genotypes for seed yield in different agro-climatic zones of Chhattisgarh - Sawargaonkar, S L; Singh, A K; Tiwari, J; Singh, K P; Sao, A; Paraye, P M; Painkra, S K; Rathia, G R; Sahu, S; Rao, S S; Sarawagi, A K; Sharma, R N; et al. (Journal of Spices and Aromatic Crops, 2020)
The present study was conducted to find out the stability and yield performances of 13 genotypes of indigenous coriander (Coriandrum sativum L.) evaluated in different agro climatic zones of Chhattisgarh. The trials were laid out in a Randomized Block Design (RBD) with three replications at three locations for three years resulting in nine environments (Genotype × year interactions). The genotypes and G × E interactions revealed significant differences at p <0.01 for seed yield indicating varieties and testing environments were distinct from each other. Additive main effects and multiplicative interaction analysis (AMMI-biplot) indicated that the yield performances of indigenous coriander genotypes were highly affected by the environments. The first two principal component axes (PCA 1 and PCA 2) were significant and they explained 67% of the total genotype x environment interaction of which 42.4% and 24.6% were represented by PCA 1 and PCA 2, respectively. A biplot generated using genotypic and environmental scores of the first two AMMI components demonstrated that genotype with larger PCA 1 and lower PCA 2 scores were high yielding and stable genotypes and genotypes with lower PCA 1 and larger PCA 2 scores were low yielding and unstable cultivars in tested locations. The genotype GC 5 C-101 (ICS 4) showed higher grain yields (16.35 q ha-1) over grand mean (13.03 q ha-1) and also had the minimum PCA 1 score, minimum AMMI stability value (ASV) and yield stability index (YSI). Therefore genotype ICS 4 (Chhattisgarh Shri Chandrahasini Dhaniya -2) showed wider stability across different agro climatic environments of Chhattisgarh.